Analysis of Tax Audit Authority from the Perspective of Appeal Disputes in the Tax Court - Benny Setiawan; Yadhy Cahyady; Supriyadi; Faisal Ahmad Chotib (Journal of Governance, Taxation and Auditing, 2026)
This study analyzes the authority of tax audits conducted by the Directorate General of Taxes (DGT) from the perspective of appeal disputes in the Indonesian Tax Court. Within Indonesia’s self-assessment tax system, tax audits function as a primary instrument for ensuring taxpayer compliance and form the basis for the issuance of Tax Assessment Letters (Surat Ketetapan Pajak/SKP). However, audit results and the resulting SKP often give rise to disputes when taxpayers question both the material correctness and the procedural legitimacy of the audit process. This research employs normative legal research with a descriptive-analytical approach, examining statutory regulations, implementing rules, and relevant Tax Court decisions concerning disputes over audit authority and procedures. The findings indicate that tax audit authority is attributive and explicitly regulated under the General Provisions and Tax Procedures Law (UU KUP) and its implementing regulations. In appeal proceedings, the Tax Court assesses both formal aspects—such as compliance with audit procedures and authority—and material aspects relating to the accuracy of tax calculations. Procedural violations do not automatically invalidate a Tax Assessment Letter; instead, judges evaluate the seriousness of the violation and its impact on taxpayer rights and material truth. The study concludes that the Tax Court plays a crucial role in controlling the use of audit authority while balancing legal certainty, protection of taxpayer rights, and the state’s fiscal interests.